Imperial Legacies: The Historical Layers of a Maghrebi Society (1860 – 1930) - (:unkn) unknown (My University, 2017)
A close study of the trans-Mediterranean legal conflicts prompted by the death of a former Tunisian minister in Florence in 1887, this article calls for a new interpretation of the history of modern North Africa. Rather than focusing on a close reading of colonial primary sources or depending on a single colonial temporality, this new interpretation must incorporate other analytical frameworks. It must also consider the overlap of French and Ottoman imperial temporalities that persisted across the Mediterranean until the 1920s, as well as the increasing number of litigations initiated before the French colonization of Tunisia—legal cases that were still influencing the rationales of North Africans during the colonial period. Analyzing these litigations not only in terms of their colonial context but also according to other temporalities, as well as diversifying our sources, allows us to nuance the commonplace, often reiterated in scholarly works on colonial North Africa, that there is a dearth of so-called “local” documentation. North African men and women involved in litigations contributed alongside Europeans to the writing of a huge amount of legal evidence and literary tracts, including in Arabic. Such sources were not always filed in the colonial archive. They are, however, of paramount importance for conceiving the modern history of North Africa in new ways.
Keywords: African Research